Durability of Multifunctional Coatings Made with Additions of Animal Waste and Agro-Industrial By-Products - Irina Popa; Cristian Petcu; Alexandrina Mureșanu (Chemistry Proceedings)
Agriculture and agriculture-related industries generate many different forms of by-products and waste, whose integration into the circular economy still requires experimental studies and research. This research aimed to obtain innovative coatings containing agro-industrial by-products and animal waste, characterizing the thermal insulation potential of the resulting products, and determining the durability of the respective coatings by exposing them to the action of an aggressive environment with large temperature variations.